2010
DOI: 10.4142/jvs.2010.11.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of German chamomile oil application on alleviating atopic dermatitis-like immune alterations in mice

Abstract: Historically, German chamomile (GC) oil has been used for treatment of skin disorders. BALB/c mice were sensitized twice a week with 100 µL of 1% 2,4-dinitrochlorobenzene (DNCB) and challenged twice the following week with 100 µL of 0.2% DNCB for atopic dermatitis induction. Thereafter, 3% GC oil was applied daily (70 µL, 6 times week) on the dorsal skin for 4 weeks. Saline or jojoba oil was used for the control mice. Blood was collected after second DNCB challenge, and at 2 and 4 weeks after initiating oil ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
1
47
0
4
Order By: Relevance
“…2,4-Dinitrochlorobenzene induces hemorrhages, itching, edema, scarring, dryness, and AD-like skin lesions on the face, nose, ears, neck, and back of BALB/c and NC/Nga mice (Lee et al, 2010;Choi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2,4-Dinitrochlorobenzene induces hemorrhages, itching, edema, scarring, dryness, and AD-like skin lesions on the face, nose, ears, neck, and back of BALB/c and NC/Nga mice (Lee et al, 2010;Choi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chamomile also contains high levels of coumarins, hydroxycoumarins, terpenoids, and is one of the richest sources of dietary antioxidants (McKay and Blumberg, 2006; Srivastava et al, 2010; Kato et al, 2008; Carnat et al, 2004). In cell culture, chamomile has been demonstrated to modulate the production of many pro-inflammatory mediators such as superoxide anion, tumor necrosis factor-alpha, interleukins and prostaglandins by selectively targeting cyclooxygenase-2 (Yoo et al, 2009; Smolinski and Pestka, 2003; Lee et al, 2010; Srivastava et al, 2009). We have demonstrated that chamomile inhibits the production of nitric oxide and inducible nitric oxide synthase in a dose-dependent manner without causing toxicity to murine macrophages (Bhaskaran et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Patients in the essential oil group experienced a lower scratching frequency compared to patients in the control group [38]. Peristomal skin problems can cause numerous unpleasant symptoms such as skin discoloration, pain, full-thickness wounds and itching.…”
Section: German Chamomile Oilmentioning
confidence: 99%